Economic Development and Entrepreneurship in Transition Economies Issues, Obstacles and Perspectives - Ateljević, Jovo; Trivić, Jelena (Springer International Publishing : Imprint: Springer, 2016)
This book contributes to a better understanding of entrepreneurship in transition economies. Current literature reflects the more traditional schools of thought on entrepreneurship, which are influenced by the Western perspective, and fail to fully address the scenario in transition economies. There is a broad consensus among academics, policy makers, and practitioners that a fundamental cause of difficulties experienced by most economies in transition has been the fact that reform has not been accompanied by the creation of new, private businesses, and particularly SMEs. This is especially evident in states created in Europe after the dissolution of the Soviet Union where many barriers, which were inherited from the old system, remain in place, thus inhibiting entrepreneurial progress in these countries despite a favorable political and economic environment. The contributions featured in this book focus on how much progress has been achieved so far with regard to these aspects, as well as identify which current barriers and issues still need to be resolved. Themes include innovation performance, financing, venture capital, educational factors, and entrepreneurial learning. .